APLIKASI SITE LOCATOR BERBASIS ANDROID - Adiwisanghagni, Mohammad; Suyanto, Mohammad; Sudarmawan, Sudarmawan (Informasi Interaktif, 2018)
Often the emergence of less effective and efficient problems in the search for the nearest BTS with the location of complaints from the customer and VIP customer XL provider underlies the request of NetOptim Department PT. Huawei Service to build a tool to facilitate their work. Based on these problems, then conducted a search research location to solve the problems Engineering by designing the concept of searching the nearest site that will be applied to an android application using the SQL Haversine formula. The goal is to measure the accuracy of the SQL Haversine Formula compared to manual system calculations and and build an application prototype that can be used as the nearest BTS location search tool from XL operator based on longitude and latitude complaint. Research method using Prospective Case Study which will be developed with Action Research.Data obtained by observation and interview method to get Gcell or BTS Database operator XL and and customer complaints, VIP and sales complaints data. The nearest complaint location with BTS data, will be processed for comparison of manual system distance calculation and distance calculations using SQL Haversine formula.      From validation analysis of SQL Haversine formula calculation, the result of the presentation of accuracy is 84.23% and the resutl of imprecise accuracy is 15.77% due to error data on the calculation.Which means, the SQL Haversine formula is considered sufficient to meet the expectations to apply in application of andorid-based site locator.Keyword: site locator, longitude, latitude, BTS, haversine